2018
DOI: 10.15252/embj.201796831
|View full text |Cite
|
Sign up to set email alerts
|

Atypical APC/C‐dependent degradation of Mcl‐1 provides an apoptotic timer during mitotic arrest

Abstract: The initiation of apoptosis in response to the disruption of mitosis provides surveillance against chromosome instability. Here, we show that proteolytic destruction of the key regulator Mcl‐1 during an extended mitosis requires the anaphase‐promoting complex or cyclosome (APC/C) and is independent of another ubiquitin E3 ligase, SCFFbw7. Using live‐cell imaging, we show that the loss of Mcl‐1 during mitosis is dependent on a D box motif found in other APC/C substrates, while an isoleucine‐arginine (IR) C‐term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…The activation of the intrinsic pathway in cells exhibiting mitotic catastrophe induced by paclitaxel aims at inducing mitotic cell death. Accordingly, the pro‐survival factor MCL‐1 has been proposed to play an important role in defining the cell fate in cancers . To directly test this, we first incubated OVCAR‐3 cells with the combination paclitaxel/proTAME, and after 6–8 hr, we added the potent MCL‐1 inhibitor A1210477 that acts as BH3 mimetic specifically targeting MCL‐1 and disrupts the MCL‐1/BIM complex .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The activation of the intrinsic pathway in cells exhibiting mitotic catastrophe induced by paclitaxel aims at inducing mitotic cell death. Accordingly, the pro‐survival factor MCL‐1 has been proposed to play an important role in defining the cell fate in cancers . To directly test this, we first incubated OVCAR‐3 cells with the combination paclitaxel/proTAME, and after 6–8 hr, we added the potent MCL‐1 inhibitor A1210477 that acts as BH3 mimetic specifically targeting MCL‐1 and disrupts the MCL‐1/BIM complex .…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the pro-survival factor MCL-1 has been proposed to play an important role in defining the cell fate in cancers. 18,21 To directly test this, we first incubated OVCAR-3 cells with the combination paclitaxel/proTAME, and after 6-8 hr, we added the potent MCL-1 inhibitor A1210477 that acts as BH3 mimetic specifically targeting MCL-1 and disrupts the MCL-1/ BIM complex. 30 Time-lapse microscopy showed that while control cells completed mitosis normally (2.26 hr), paclitaxel significantly increased the average mitosis duration up to 13.7 hr, which was followed by mitosis escape and the formation of tetraploid cells ( Figs.…”
Section: Sequential Addition Of An Mcl-1 Inhibitor To the Combinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The controversy still exists as to which E3-ligases control MCL1 levels in response to different types of stress including mitotic arrest [8,20]. One E3-ligase that has been shown to regulate BCL2 family proteins is membrane associated RING finger protein 5 (MARCH5) [21,22].…”
Section: Introductionmentioning
confidence: 99%